Primary MCL Repair Following Distal Avulsion: A Technique Video - Brian Forsythe MD; Daanish Khazi-Syed BS; Joshua H. Chang BS; Vahram Gamsarian BE; Jonathan Spaan BS; Vikranth Mirle BS; Monique Haynes MD; Eric J. Cotter MD (Video Journal of Sports Medicine)
Background: The medial collateral ligament (MCL) is the most frequently injured knee ligament, accounting for approximately 8% of all knee injuries. This video presents a reproducible method for MCL repair. Indications: Grade 1, grade 2, and proximal grade 3 MCL tears with no concomitant injuries are managed nonoperatively with a hinged knee brace and physical therapy. Complete, distal MCL tears, often presenting as Stener-like lesions, warrant surgical intervention due to their tendency for inadequate healing with conservative measures. Technique Description: An 8-cm incision is made centered over the pes tendons a finger breath lateral to the posterior medial border of the tibia. Full-thickness medial and lateral soft tissue flaps are made sharply, exposing the sartorial fascia. An L-shaped incision is made through the fascia, proximal to the hamstring tendons and superiorly and just medial to the tibial tubercle. The superficial MCL is visualized, lifted off the tibia with a Cobb elevator, and captured with 2 suture tapes in a whipstitch fashion. A relatively isometric MCL insertion point is identified, unicortically drilled, and tapped for a suture anchor. The suture tapes are loaded into the anchor, tensioned, and screwed into position with the knee flexed between 10° and 30°. The 2 separate suture tapes are tied together to reinforce fixation, and the anterior margin of the MCL is then sutured to the periosteum to reinforce the repair. Results: The patient returned to full function and activity after 6 months. Repair of acute MCL injuries is known to show favorable outcomes. There are currently no published data on the specific MCL repair technique presented in this level 5 evidence video. Discussion/Conclusion: Repair of distal MCL avulsions can be technically challenging. The technique presented is a reproducible method for MCL repair. Earlier surgical intervention may optimize outcomes and obviate the need for allograft reconstruction. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.